The impact of management control systems on performance: evidence from Vietnamese enterprises / Huy Manh Dao, Son Van Dinh and Oanh Thi Tu Le - Huy, Manh Dao; Son, Van Dinh; Oanh, Thi Tu Le (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
The study aimed to evaluate the impact of management control systems (MCS) on the performance of enterprises through the mediated role of learning orientation and entrepreneurial orientation. This study was based on a huge amount of empirical data that was collected from 308 participants, including accountants, CEOs, and business unit managers of Vietnamese firms. Structural equation modeling was used to assess the research model. Our main findings showed that: (1) Both Diagnostic and Interactive MCS uses had a positive impact on performance; (2) Only Interactive MCS use generated a significant, positive, and direct effect on Entrepreneurial Orientation (EO); (3) Learning Orientation (LO) had a direct impact on performance; however, Entrepreneurial Orientation (EO) had not enough evidence to evaluate this effect. This study contributes important proof of the positive impact of MCS on performance. These findings provide precious scientific knowledge for firm managers in Vietnam to improve organizational performance by using MCS, learning orientation, and entrepreneurial orientation.